KONSEP UANG DALAM EKONOMI ISLAM - Mardinai Sulastri Hasibuan (Adpertens: Jurnal Ekonomi dan Manajemen, 2024)
Humans have used money as a tool for transactions for a long time. Money is used as the official currency since the time of the Prophet Muhammad. and passed on by the Caliphs thereafter for centuries were gold dinars and silver dirhams. This paper aims to lay out the concept of money according to Islamic economics. For this purpose, the normative legal study method is used in the writing. Data taken from primary and secondary data sources. Among the findings of this study is that from the perspective of Islamic economics, money is anything that is generally accepted and published by authorized financial institutions as a medium of exchange and a measure and store of value. In addition, the use of gold dinars and silver dirhams is not a religious obligation, but history has shown that these two currencies are very stable and are not subject to inflation like paper money. According to the Islamic economic perspective, money has three functions, namely as a medium of exchange, as a unit of calculation or measure of value, and as a store of value when money is made of gold and silver. In the financial sector, Islam has many provisions, including the use of money as a means of measuring the nisab and levels of zakat, dowry, kaffarah, nisab cut hands for thieves, diyat and jizyah.